Metal-THINGS: on the metallicity and ionization of ULX sources in NGC 925 - Lara-López, Maritza A.; Zinchenko, Igor A.; Pilyugin, Leonid S.; Gunawardhana, Madusha L. P.; López-Cruz, Omar; Sullivan, Shane P. O'; Feltre, Anna; Rosado, Margarita; Sánchez-Cruces, Mónica; Chevallard, Jacopo; Rossi, Maria Emilia De; Dib, Sami; et al. (The astrophysical journal, 2021)
We present an analysis of the optical properties of three Ultra Luminous X-ray (ULX) sources identified in NGC 925. We use Integral field unit data from the George Mitchel spectrograph in the context of the Metal-THINGS survey. The optical properties for ULX-1 and ULX-3 are presented, while the spaxel associated with ULX-2 had a low S/N, which prevented its analysis. We also report the kinematics and dimensions of the optical nebula associated with each ULX using ancillary data from the PUMA Fabry-Perot spectrograph. A BPT analysis demonstrates that most spaxels in NGC 925 are dominated by star-forming regions, including those associated with ULX-1 and ULX-3. Using the resolved gas-phase metallicities, a negative metallicity gradient is found, consistent with previous results for spiral galaxies, while the ionization parameter tends to increase radially throughout the galaxy. Interestingly, ULX-1 shows a very low gas metallicity for its galactocentric distance, identified by two independent methods, while exhibiting a typical ionization. We find that such low gas metallicity is best explained in the context of the high-mass X-ray binary population, where the low-metallicity environment favors active Roche lobe overflows that can drive much higher accretion rates. An alternative scenario invoking accretion of a low-mass galaxy is not supported by the data in this region. Finally, ULX-3 shows both a high metallicity and ionization parameter, which is consistent with the progenitor being a highly accreting neutron star within an evolved stellar population region.